Comparative Assessment of Performance and Emission Characteristics of a C.I. Engine Using Biodiesel and Gtl (Gas to Liquid) Fuel - Tripathi, Anurag; Singh, Vineet; R. Mishra, V.; Nigam, Akash; Kumar, Niraj; Maheswari, Anurag (International Journal of Engineering and Technology, 2018)
Today we are worry due to hiking the prize of diesel fuel. Fossil fuels are main cause of environmental problem like air pollution, global warming and health related problem. Therefore, in this paper our main concerned about to study the performance parameter on CI engine by using diesel fuel, jatropha biodiesel (B20), Gas to liquid (GTL) diesel. Experimental study shows that GTL fuel produce lower amount of unburned hydrocarbon, carbon monoxide, carbon dioxide, smoke etc compared with the diesel fuel. We have also observed that brake specific fuel consumption is low in GTL engine as compared with the conventional diesel engine even the nitrogen oxide formation is also low compared with jatropha biodiesel (B20).Â Â